Mesoporous SiO2/carbon hollow spheres applied towards a high rate-performance Li-battery anode. Issue 11 (21st September 2016) - Wang, Chien-Wen; Liu, Kung-Wen; Chen, Wei-Fu; Zhou, Jing-De; Lin, Hong-Ping; Hsu, Chun-Han; Kuo, Ping-Lin
Abstract : The continuous carbon network and the fast transport of Li ions through the SiO2 shell contribute to a high-rate performance. Abstract : Mesoporous SiO2 /C hollow spheres have been successfully synthesized via a one-step template process and carbonization of a mesoporous SiO2 /poly(ethylene oxide)/phenolic formaldehyde resin hollow nanocomposite, and then evaluated as anode materials for lithium-ion batteries. The continuous carbon framework significantly led the SiO2 /C hollow spheres to reach a high conductivity (3.9 × 10 −4 S cm −1 ) compared with the SiO2 hollow spheres (<10 −9 S cm −1 ), furthermore, the unique hollow nanostructure with a large volume interior and numerous mesopores plugged with carbon in the silica shell, could accommodate the volume variation and improve the structural strain for Li ion conduction, as well as allow rapid access of Li ions during charge–discharge cycling. For battery applications, at 100 mA g −1 charge/discharge rates, the reversible capacity of this mesoporous SiO2 /C anode (624 mA h g −1 ) is over ten times higher than that of the SiO2 anode (61 mA h g −1 ). More specifically, even under the high discharge rate of 3000 mA g −1, this SiO2 /C hollow nanostructure exhibits a specific capacity of 582 mA h g −1, featuring a high retention of more than 90% of its low discharge rate of 100 mA g −1 . This demonstrates that the effective conduction of electrons through the continuous carbon network and the fast transport of Li ions through the nanoscale SiO2 shell significantly contribute to the high-rate performance.